Science Integration Model Project in Islamic Studies Learning (Research at Islamic Junior High School Bani Hasyim Singosari Malang) - A’yun, Qurroti; Fauziyah, Novi Maulia; Nuranisaturofiah, Ayu; Mefia, Ninda Eka Artha; Andini, Salwa Triajeng (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
At Bani Hasyim Singosari Islamic Junior High School, integration is emphasized as an essential quality for practicing learning. The aim of integrated learning is for students to have a holistic understanding and always instill faith in God, the Creator, in everyday life. The author intends to conduct in-depth, systematic and objective research on the topic of how Islamic Religious Education in this school integrates science and religion in education. This research is qualitative in nature and uses a case study approach, descriptive methods, observation, interviews, documentation and triangulation for data collection. Qualitative field research is the term for this type of research. The data analysis method uses data reduction, data presentation, and drawing conclusions. Research findings show: (1) In this school, learning Islamic subjects combines the idea of science integration by applying Islamic principles to science. Making the Qur'an the main basis or source of knowledge; b) Cultivate problems in Islamic Studies material and stay away from information barriers; c) Developing the Character of Ulil Albab; d) Following the verses of the Koran that discuss science; e) Creating school curricula in educational institutions. (2) Scientific integration in this school uses an integration pattern in learning, where a teacher takes one of the major themes of Islamic Religious Education and its uniqueness, then integrates or strengthens it with scientific knowledge.